Women in Policing: A Longitudinal Assessment of Female Officers in Supervisory Positions in the New York City Police Department. Issue 1 (1st January 2016) - Guajardo, Salomon Alcocer
Abstract : This study examined the growth in the number of female officers in supervisory and command positions (i.e., sergeant to bureau chief) in the New York City Police Department (NYPD) from 2000 to 2013. Time and annual percent changes in the number of male officers, the number of male officers in supervisory and command positions, and the number of female officers served as predictors. An ordinary least squares regression analysis failed to produce statistically significant results for the growth in the number of female officers in supervisory and command positions. The regression analysis also produced statistically nonsignificant results for changes in the level of disparity among male and female officers in supervisory and command positions. Over the past 13 years, female officers have made little progress in advancing to supervisory and command positions in the NYPD.